1991
DOI: 10.1099/0022-1317-72-7-1667
|View full text |Cite
|
Sign up to set email alerts
|

Parameters influencing the attachment of hepatitis A virus to a variety of continuous cell lines

Abstract: We have investigated the interactions of purified radiolabelled hepatitis A virus (HAV) with a variety of continuous cell lines. Virus labelled either in vitro with radiolabelled iodine or in vivo with radiolabelled uridine bound to cells with similar efficiency. Attachment to BS-C-1 cells was calcium ion-dependent and this correlated with infectivity assay results. The cell tropism of HAV attachment was examined using cell suspensions and confluent cell monolayers at both 4 °C and 37 °C. The maximum level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
19
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…The uncoating of HAV has been demonstrated to be a slow and asynchronous process (3,5,9,30). By contrast, the attachment to and penetration of cells by HAV appear to be as efficient as for other picornaviruses (3,8,29,32).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The uncoating of HAV has been demonstrated to be a slow and asynchronous process (3,5,9,30). By contrast, the attachment to and penetration of cells by HAV appear to be as efficient as for other picornaviruses (3,8,29,32).…”
mentioning
confidence: 96%
“…The uncoating of HAV has been demonstrated to be a slow and asynchronous process (3,5,9,30). By contrast, the attachment to and penetration of cells by HAV appear to be as efficient as for other picornaviruses (3,8,29,32).Intact, antigenic particles from HAV-infected cells or cell culture supernatants have recently been demonstrated to be of three types: (i) virions, containing capsid proteins VP1, VP2, VP3, and possibly VP4 and viral RNA; (ii) provirions, or "immature" virions, containing VP1, VP0, VP3, and viral RNA; and (iii) procapsids, which are empty HAV particles with the same capsid composition as provirions but lacking RNA (2, 7, 23). Provirions have been implicated as direct precursors of mature picornavirus virions via the cleavage of VP0 (to VP2 and VP4) in an RNA-dependent manner (6).…”
mentioning
confidence: 99%
“…Although cell lines originating from tissues other than liver, such as fibroblasts and kidney cells, are also susceptible to HAV infection (9, 11) and although HAV antigen and the putative receptor for HAV could be detected in different organs, such as kidney, spleen, and gastrointestinal tract (2, 6, 10, 18), no extrahepatic sites of HAV replication have been clearly identified. The data on the ubiquitous expression of a receptor for HAV and the ability of HAV to replicate in a number of nonliver cells in cell cultures, but obviously not in the organism, suggest that HAV may be targeted to the liver by a particular mechanism.Data from several laboratories showed that HAV virions are partially associated with immunoglobulin A (IgA) molecules (19,22) and other host organism-derived materials, such as fibronectin or ␣ 2 -macroglobulin (21,23,24,35,43). As viruses may find entry into host cells via receptors specific for molecules of the host organism ligated to the virion (13,16,20,26) and as the liver plays a central role in IgA metabolism by eliminating IgA as well as antigen-IgA complexes (4), we wondered if HAV-specific IgA ligated to HAV supports the targeting of HAV to the liver and is able to mediate the entry of HAV into hepatocytes via receptors specific for the IgA molecule and if such a carrier-mediated mechanism may result in viral infection.…”
mentioning
confidence: 99%
“…Data from several laboratories showed that HAV virions are partially associated with immunoglobulin A (IgA) molecules (19,22) and other host organism-derived materials, such as fibronectin or ␣ 2 -macroglobulin (21,23,24,35,43). As viruses may find entry into host cells via receptors specific for molecules of the host organism ligated to the virion (13,16,20,26) and as the liver plays a central role in IgA metabolism by eliminating IgA as well as antigen-IgA complexes (4), we wondered if HAV-specific IgA ligated to HAV supports the targeting of HAV to the liver and is able to mediate the entry of HAV into hepatocytes via receptors specific for the IgA molecule and if such a carrier-mediated mechanism may result in viral infection.…”
mentioning
confidence: 99%
“…per well) at 4 mC for 2 h. HAV used as the inoculum was sucrose density gradient-purified, radiolabelled, column-sieved, density gradient-purified again to remove free radioisotopes and resuspended in Dulbecco's modified MEM (Zajac et al, 1991). Cultures were washed with PBS three times and solubilized with 1 % SDS.…”
mentioning
confidence: 99%